Erzählte Argumente. (Studien und Texte Zur Geistesgeschichte des Mittelalters Ser., 2017)
In Erzählte Argumente. Exempla und historische Argumentation in politischen Traktaten c. 1265-1325 , Jacob Langeloh describes how medieval political writers around the year 1300 employed historical arguments. Scholastic authors are commonly thought to be oblivious to history. This study shows that they not only showed great respect for historical arguments, but that they also displayed a refined technique in using them. In addition to case studies ranging from Thomas Aquinas to Dante Alighieri and up to Marsilius of Padua, Jacob Langeloh also offers a functional description of both Exempla and narrated historical argument.